2001
DOI: 10.1055/s-2001-14929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Hypoxia on Leptin, Insulin, Growth Hormone and Body Composition in the Rat

Abstract: The purpose of the present study was to evaluate the effect of exposure to hypoxia from birth to 7 days of age on leptin, insulin, growth hormone (GH), insulin-like growth factor-1 (IGF-1), glucose, corticosterone, body weight, and body composition in rats studied at 7 days of age and then after return to normoxia. Hypoxia for the first 7 days of life resulted in a significant decrease in plasma leptin, body weight, and an increase in corticosterone and insulin with no change in plasma glucose, GH or IGF-1. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 23 publications
5
47
2
2
Order By: Relevance
“…It is possible that the marked increases in adiponectin in the current study were in response to the decrease in insulin sensitivity we have previously demonstrated ( 7,9,12 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is possible that the marked increases in adiponectin in the current study were in response to the decrease in insulin sensitivity we have previously demonstrated ( 7,9,12 ).…”
Section: Discussionmentioning
confidence: 65%
“…We have also demonstrated that ghrelin, a hormone released by the GI tract that has a wide variety of endocrine and metabolic actions, is increased by dexamethasone therapy ( 15 ). The differential actions of leptin and ghrelin on food intake, insulin sensitivity, and metabolic function made it clear that these two factors per se could not account for the changes in growth hormone ( 7 ), IGF-I ( 8 ), body composition ( 7,8 ), weight gain ( 7,8 ), lipid profiles ( 12,14 ), and other parameters of metabolic function in our previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the newborn to adapt to low O 2 depends on a multitude of physiological changes. These changes include, but are not limited to, shifts in metabolic, hemodynamic, digestive, and cardiorespiratory function (2,6,10,13,14,17,21,26,35). It has also become evident that there exists a unique developmental aspect to the maturation of the adrenocortical response to stress in the neonatal rat (1,33,37,38).…”
mentioning
confidence: 99%
“…Neonatal hypoxia has profound effects on intermediary metabolism (2,6,13,26,27), including significant increases in plasma lipids (i.e., total cholesterol, free fatty acids, and triacylglycerides; see Ref. 27).…”
mentioning
confidence: 99%